GAINING ACCEPTIBILITY USING DESIGN THINKING IN FUNDAMENTAL TRANSLATION CLASS - Nadia Gitya Yulianita; Dyah Raina Purwaningsih (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
This paper points on the use of design thinking in fundamental translation class. Design thinking is an approach to produce the best solution of a problem. This approach includes five steps, namely empathize, define (the problem), ideate, prototype, and test. The researchers focus on the translation’s acceptability of idioms since this topic is usually problematic to students. Therefore, a case study was conducted in this research. The participants of this research were 20 students of fundamental translation class in English Literature Study Program, Universitas Jenderal Soedirman. The students translated some idioms using design thinking and their translations were randomly selected. Observation was conducted to examine the students’ behaviours in translating idioms. After that, the researchers rated their translations’ acceptability. The results indicate that design thinking’s application in translating idioms produce acceptable translations. Furthermore, this study can be beneficial for translators and translation teachers to gain acceptability in translation.